Memahami Budaya Bangsa Asing melalui Tarian Adat untuk Meningkatkan Kompetensi Individual Deference Siswa Darul Muhmin School, Satun Thailand - Syahfitri, Ayunda; Wastuti, Sri Ngayomi Yudha; Hasibuan, M Fauzi (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to understand the comprehension of foreign cultures through traditional dances, enhance students' competence, and shape character. Qualitative method was used with a case study at Darul Muhmin School. The results indicate that traditional dances shape students' understanding of cultural diversity, improve character, and assists students face global challenges. Integrating traditional dances into the curriculum contributes to shaping students' character to be open, tolerant, and ready to face global challenges. The role of teachers and curriculum planning is crucial in providing deep and relevant learning experiences for students, ensuring that cultural diversity becomes an integral part of this school.